Pengaruh Pemberian Air Rebusan Mahkota Dewa (Phaleria Macrocarpa (Scheff) Boerl) Terhadap Kadar Asam Urat Darah Pada Wanita Menopause - Didien Ika S; Erni Dwi E; Ari Kusmiwiyati (Politeknik Negeri Jember, 2017)
Uric acid is the final result of purine metabolism in the body, which excreted through urine. In gout conditions, there is uric acid crystals deposit in joints. In the women's uric acid levels did not increase until menopause because estrogen helps to increase spending uric acid in the kidneys by reducing the amount of uric acid reabsorption. Phaleria macrocarpa (Scheff) Boerl is a plant that has medicinal properties to treat gout because Phaleria macrocarpa (Scheff) Boerl contains flavonoids that can lower uric acid by the mechanism of resistance to the activity of xanthine oxidase on purine bases so that it will reduce production of uric acid. The purpose of this study was to determine the effect of giving Phaleria macrocarpa (Scheff) Boerl’s decoction water on uric acid’s level in postmenopausal women in RW 01 Kelurahan Kebonsari Sukun Malang. This research is Pre Experiment with one group pre-post test design. Using 24 postmenopausal women who suffer from uric acid with total sampling technique. Test data analysis using the Wilcoxon Signed Rank Test on the significant level α = 0.05. The results showed 87.5% of respondents had decreased levels of uric acid and 12.5% of respondents did not experience changes in uric acid’s level or are likely to remain. Results of analysis of test data with Wilcoxon Signed Rank Test Zhitung obtained (-4.02) < ZTable (1,96). It’s means there is influence of Phaleria macrocarpa (Scheff) Boerl’s decoction water to reduction of uric acid levels in postmenopausal women. Referring to these results it is expected that Phaleria macrocarpa (Scheff) Boerl can be used as therapy in the treatment of gout.